2017
DOI: 10.1021/acs.jpcc.7b07360
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Nano- and Mesoscales on Macroscopic Cation Conductivity in Perfluorinated-Sulfonic-Acid Membranes

Abstract: A mean-field local-density theory is outlined for ion transport in perfluorinated-sulfonic-acid (PFSA) membranes. A theory of molecular-level interactions predict nanodomain and macroscale conductivity. The effects of solvation, dielectric saturation, dispersion forces, image charge, finite size, and confinement are included in a physically consistent 3D-model domain geometry. Probability-distribution profiles of aqueous cation concentration at the domain-scale are in agreement with atomistic simulations using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 74 publications
1
27
0
Order By: Relevance
“…Hydrophilic domain spacing, ordering, and connectivity are important parameters related to phase separation that determine transport pathways. These morphology features need to be understood to construct relationships between molecular structure and ion conductivity . SAXS can reveal the degree of phase separation in ionomer membranes.…”
Section: Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hydrophilic domain spacing, ordering, and connectivity are important parameters related to phase separation that determine transport pathways. These morphology features need to be understood to construct relationships between molecular structure and ion conductivity . SAXS can reveal the degree of phase separation in ionomer membranes.…”
Section: Results and Discussionmentioning
confidence: 99%
“…This suggests subtle chemistry differences could play a role in nanoswelling of domains and overall conductivity. Modeling and simulation studies have shown that electrostatic interactions within polymer-bound anionic groups and cation solvation energy have the greatest impact on charge migration at the molecular and domain scale, and this is influenced by the chemistry and resulting charge delocalization on the side-chain. , Previous work has shown that the proximity of protogenic groups and the charge delocalization on the side-chain are important factors that dictate hydrogen bonding and proton dissociation at low hydration levels . PFICE ionomers have a side-chain chemistry and combination of protogenic groups that facilitates water hydrogen-bonding configurations promoting proton dissociation, as illustrated in Figure .…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The change in the slope of conductivity against hydration was previously reported for proton-form PFSAs, and associated with the ion exchange capacity and more recently modeled to be related to mesoscale network tortuosity. 6,60 Conductivity of an interconnected water domainnetwork as a function of the domain volume fraction is expressed as:…”
Section: 3mentioning
confidence: 99%
“…In recent years, nano-confined structures have been exploited in the study of cost-effective and reliable polymer architectures for electrochemical devices [ 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ]. Understanding the water structure and the behavior of ions in these confined structures is essential to gain insight into the ion diffusion mechanisms.…”
Section: Introductionmentioning
confidence: 99%